Betydningsbeskrivelse og prototypeteori - Hovmark, Henrik (LexicoNordica, 2012)
Prototype theory has been put forward as a useful tool in lexicographic theory and practice. In this article I discuss the use of prototype theory in lexicographic word sense definition. I suggest that many lexicographic practices already build upon ideas similar to prototype theory but that the theory can make lexicographic work more consistent and systematic. However, the main contribution of prototype theory (and cognitive semantics) would seem to be an increased focus on data and methods, favoured by close connections between strands of corpus linguistics, cognitive linguistics and lexicography.